1000 voices: preliminary analysis of paediatric admissions to English Voluntary Hospitals for 1756 and 1779. (24th May 2012) - Sharma, R; Levene, A; Williams, AN
Abstract : Introduction: Recent scholarship has overturned the myth that, 'Pediatrics as a specialised branch of medicine had no real existence before the middle of the nineteenth century, hence the literature on the subject is meagre.'1 Paediatric admissions were frequent in voluntary hospitals in the mid eighteenth-century well before the first specialty hospital2 . We present further analysis of data on 1483 paediatric admissions at 5 voluntary hospitals in 1756 and 1779. Method: Data was collected on all inpatients and outpatients at Chester Infirmary, Manchester Royal Infirmary, Northampton General Hospital, Royal Victoria Hospital Newcastle and Bristol Royal Infirmary in 1756 and 1779. Patients under 18 years were sub-grouped and analysed using SPSSv20. "Distempers" were grouped into diagnostic and systemic categories. Results: Mean age at presentation was 11.24 years (SD=5.3 years). The mean duration of illness prior to admission was 12.3 months (SD=23.4 months). 42% were female and 58% male. Febrile illness was the most common presentation (12.5%). There was a significant variation in age of presentation across the hospitals (p<0.001) with mean age at presentation being 9.25 years (SD=5.44 years) at Manchester Royal infirmary and 13.8 years (SD-=4.1 years) in Bristol 1779. Females presented approximately 1 year later than males (p<0.001) and were also unwell for longer prior to admission (p<0.001). There was no significant association between the "Distemper" and the hospital to which the patient was admitted (Lambda=0.21). There was no significant difference in outcome between hospitals (Lambda=0.09). Conclusions: There is significant variation in age of admission to different hospitals. Febrile illness is a significant disease burden reflecting the concerns of hospital administrators at the time. There is a gender bias in the presentation of children in the mid eighteenth-century. There is no evidence to suggest sub-specialisation in paediatrics in the different hospitals.